An Empirical Study on Sales Promotion of Dabur India Limited in Indian Rural Market - Malik, Garima (Indian Journal of Marketing, 2011)
The Indian rural market is witnessing a boom of late, all very thanks to the saturation being witnessed by the urban counterparts and with the advent of economic slowdown in the economy, the corporates are now on a hunch to look out for greener pastures where it can sell their offerings at reasonable profits. There is an intense competition in the market and none of the corporate wants to lose the golden opportunity offered by the great Indian rural market. India's premier economic research entity NCAER, recently confirmed that the rise in rural income is keeping pace with urban incomes. From 55 to 58 percent of the average urban income in 1994-95, the average rural income has gone up to 63 to 64 percent by 2001-02 and touched almost 66 percent in 2004-05. This study was conducted to gain insight into the perception of rural consumers about various promotional measures adopted by Dabur India. The X2 test was applied to test the effectiveness of sales promotion strategies adopted by the company and some useful implications for company have been offered at the end.